2022
DOI: 10.3390/f13020226
|View full text |Cite
|
Sign up to set email alerts
|

Kinship Analysis and Pedigree Reconstruction of a Natural Regenerated Cork Oak (Quercus suber) Population

Abstract: Cork oak (Quercus suber L.) is a valuable forest species in the western Mediterranean Basin due to its ecological value and the production of cork (a renewable natural material). Cork quality depends on the genetic background and cork oak environment, which has long been recognized. As no cork oak genetic trials with pedigree information were available, the inference of the genetic relatedness between individuals from molecular markers can potentially be applied to natural populations. This work aimed to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The recent developments of high-throughput sequencing technologies have facilitated the sequencing of entire genomes, supporting the development of new genomic resources and identifying single-nucleotide polymorphism (SNP). Mendes et al [46] investigated the potential of performing kinship prediction and pedigree reconstruction by SNP genotyping in a natural regenerated cork oak population. Kinships were successfully identified, and some families' pedigrees were established, which support that pedigree information can be a valuable tool for future management strategies of cork oak populations, including future cork oak breeding schemes [46].…”
Section: Hybrid Parental Species Reference Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent developments of high-throughput sequencing technologies have facilitated the sequencing of entire genomes, supporting the development of new genomic resources and identifying single-nucleotide polymorphism (SNP). Mendes et al [46] investigated the potential of performing kinship prediction and pedigree reconstruction by SNP genotyping in a natural regenerated cork oak population. Kinships were successfully identified, and some families' pedigrees were established, which support that pedigree information can be a valuable tool for future management strategies of cork oak populations, including future cork oak breeding schemes [46].…”
Section: Hybrid Parental Species Reference Observationsmentioning
confidence: 99%
“…Mendes et al [46] investigated the potential of performing kinship prediction and pedigree reconstruction by SNP genotyping in a natural regenerated cork oak population. Kinships were successfully identified, and some families' pedigrees were established, which support that pedigree information can be a valuable tool for future management strategies of cork oak populations, including future cork oak breeding schemes [46].…”
Section: Hybrid Parental Species Reference Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have shown that using more SNPs can increase the number of identified kinships (Mendes et al, 2022), we chose to prioritize the creation of an SNP dataset with minimal errors by applying filtering conditions, even if it meant a reduction in the number of SNPs. This is because when a large number of SNPs were used under loose filtering conditions, the estimation of kinships did not yield satisfactory results when the assumed error rate was high in COLONY 2.0.…”
Section: Snp Filtering Criteria Suitable For Kinship Estimationmentioning
confidence: 99%